Modulating endocannabinoid signaling to treat methamphetamine relapse - Fort, Troy Douglas (My University, 2024)
Overdose deaths due to methamphetamine (meth) have risen significantly in the last decade. One system of therapeutic interest is the endocannabinoid (eCB) system. The eCB, anandamide (AEA), has previously been shown to decrease cue-induced drug craving when intracranially administered. The current project took a different therapeutic approach by inhibiting the metabolism of AEA via the fatty-acid amide hydrolase (FAAH)-inhibiting drug, URB597. Administration of URB597 has been shown to attenuate cue-induced craving for both cocaine and nicotine. We aimed to evaluate whether the efficacy of URB597 extends to cue-induced methamphetamine craving. To test this question, we administered URB597 (vehicle, 0.3, or 1.0 mg/kg; ip) daily during abstinence to extended-access meth self-administration. We then assessed cue-induced methamphetamine seeking at Withdrawal Day 2 (WD2) and Withdrawal Day 28 (WD28). Animals were sacrificed following the WD28 cue-test to assess changes in cannabinoid and glutamate receptor expression via western blot and enzyme-linked immunosorbent assay (ELISA). We did not observe that either dose of URB597 was effective in attenuating cue-induced craving at either WD2 or WD28. Results of western blot analysis indicated that meth abstinence significantly impacted the expression of cannabinoid receptor-1 and metabotropic glutamate receptor-5 in the dorsal hippocampus (dHipp), as well as the dorsomedial (dmPFC) and ventromedial prefrontal cortex (vmPFC). Finally, ELISA measurements of AEA indicated that meth did not significantly lower AEA levels as predicted. Taken together, these results further implicate the involvement of the eCB system in meth-use. However, different eCB mechanisms of action should be explored in the development of meth relapse therapeutics.
Keywords: Incubation of craving; Methamphetamine; Anandamide; Fatty-acide amide hydrolase; Endocannabinoid